PENGARUH BIAYA PRODUKSI TERHADAP LABA BERSIH PADA PERUSAHAAN SUB INDUSTRI MAKANAN OLAHAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2023 - Juwita, Rukmi; Aulia, Intan (Universitas Logistik dan Bisnis Internasional, 2025)
The impact of inflation has had a big impact on the food and beverage industry due to the surge in raw material prices, logistics costs and fuel oil which has an impact on the total cost of production. Under these conditions, of course the company will suffer the impact of stagnant profit margins and even tend to weaken. Inflation that continues to increase will cause a recession. The increase in prices of goods causes a decrease in people's purchasing power, thereby making the food and beverage industry sluggish. The phenomenon of global recession can cause company bankruptcy, because a decrease in demand will result in a decrease in company profits. The aim of this research is to find out whether there is an influence of production costs on net profit in processed food sub-industry companies. The data used in this research is secondary data. And the samples used were 42 samples of financial reports from processed food sub-industry companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2023 period. This research uses quantitative methods. The data analysis techniques used are normality test, product moment correlation analysis, simple linear regression analysis, coefficient of determination analysis, and hypothesis testing (t test). The results of the t test carried out using IBM SPSS Statistics 27, show that there is a significant influence between production costs and net profit. Keywords: Production Costs, Net Profit, Processed Food Sub-Industry